Legality and Supremacy of Law: All Actions and Policies Must Comply with Applicable Laws - Fatema Miah (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
Law of Human Right is a Critical subject matter, the Human Right Law Act in the Slavery, and Force labour is often occurred together or two separate occurrences occasionally, they are two separate matters. This falls under the act of law in the Article 4, of Human Right, the Act what is placed against the slavery and force labour. Article 4, protects people’s right that individuals should not be held in slavery or servitude. This Act is against those force labour upon others and it is to stands up for the rights of those are made to do work by force, or forced into or made to compulsory labour, and denied their Rights of refuse to accept the order or to refuse vow before the coercers or controlling group or individuals. The same Act stand up against the modern day slavery.